2014
DOI: 10.1063/1.4878416
|View full text |Cite
|
Sign up to set email alerts
|

Impact of total ionizing dose irradiation on electrical property of ferroelectric-gate field-effect transistor

Abstract: Articles you may be interested inInfluence of Ti substitution on the electrical properties of metal-ferroelectric (BiFeO3)-insulator (HfO2)-silicon structures for nonvolatile memory applications The electrical and switching properties of a metal-ferroelectric ( Bi 3.15 Nd 0.85 Ti 3 O 12 ) -insulator ( Y 2 O 3stabilized ZrO 2 )-silicon diode Appl. Phys. Lett. 97, 103501 (2010); 10.1063/1.3486464Characterization of Pt / Bi 3.15 Nd 0.85 Ti 3 O 12 / HfO 2 / Si structure using a hafnium oxide as buffer layer for fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 25 publications
0
10
0
1
Order By: Relevance
“…It can be concluded that the two polarization states of HZO ferroelectric thin films have excellent tolerance of total dose radiation. Considering the dependence of radiation-induced charge trapping on the oxide thickness, the excellent scalability of HfO 2 -based thin films would help suppress the buildup of radiation-induced oxide-trapped charges. The buildup of a large amount of oxide-trapped charges in the gate stack may cause severe Δ V ot and Δ V it in the FeFETs, resulting in poor stability of memory states under radiation. Indeed, previous studies have shown that HfO 2 -based ferroelectric thin films exhibit robust ferroelectric performance against TID radiation, while the remanent polarization of thicker perovskite ferroelectric films was reported to be degraded by the TID radiation. Thus, the HZO-based FeFETs show stable memory states under radiation, demonstrating their great potential for radiation-hard nonvolatile memory applications.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It can be concluded that the two polarization states of HZO ferroelectric thin films have excellent tolerance of total dose radiation. Considering the dependence of radiation-induced charge trapping on the oxide thickness, the excellent scalability of HfO 2 -based thin films would help suppress the buildup of radiation-induced oxide-trapped charges. The buildup of a large amount of oxide-trapped charges in the gate stack may cause severe Δ V ot and Δ V it in the FeFETs, resulting in poor stability of memory states under radiation. Indeed, previous studies have shown that HfO 2 -based ferroelectric thin films exhibit robust ferroelectric performance against TID radiation, while the remanent polarization of thicker perovskite ferroelectric films was reported to be degraded by the TID radiation. Thus, the HZO-based FeFETs show stable memory states under radiation, demonstrating their great potential for radiation-hard nonvolatile memory applications.…”
Section: Resultsmentioning
confidence: 99%
“…25−28 voltage (V TH ) shift and memory window (MW) degradation. 25,28 In 2019, Chen et al first reported the TID effect on memory characteristics of Hf 0.5 Zr 0.5 O 2 (HZO)-based FeFETs. 29 They found that the MW of HZO-based FeFETs did not degrade for the dose to 1 Mrad(Si), but the program/erase (P/ E) cycling properties (i.e., endurance properties) showed nonnegligible degradation owing to the radiation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Например, полевой транзистор [1], где в качестве подзатворного диэлектрика используется сегнето-электрический слой, который является основой долговременной энергонезависимой памяти с про-извольным доступом, высокой скорости и плотно-сти записи данных при незначительной потребляе-мой мощности. Однако в настоящее время ни одна из исследуемых сегнетоэлектрических ячеек памя-ти не позволяет хранить информацию дольше, чем несколько дней, что далеко от требуемого разра-ботчиками вычислительной техники десятилетнего энергонезависимого хранения информации [2].…”
Section: Introductionunclassified
“…The development of resistant materials in harsh radiation environments is of prime importance for the reliability of systems in aerospace, nuclear and military industries 1 . Hardening studies of micro and nanoscale electronic circuits are currently performed under irradiation doses ranging from 1 Gy to a few tens of kGy [2][3][4][5][6][7][8][9][10][11] . Strong alterations of performances are observed for doses larger than 1 kGy.…”
mentioning
confidence: 99%